PENANAMAN NILAI-NILAI PERDAMAIAN DI PEACESANTREN WELAS ASIH SAMARANG GARUT - Dewi Azhar, Rosa Kusuma; Bashori, Khoiruddin; Samsuddin, Muhammad (Universitas Muhammadiyah Surakarta, 2020)
This study aims to determine the achievements, models, and methods of inculcating the values of peace in Peacesantren Welas Asih Garut. The formation of values as the core of the goals of national education cannot be achieved instantly. It takes efforts to find alternative educational models that can be applied. Peace education is an effort made to realize values, behavior, and ways of life that support the creation of a culture of peace. This study used a qualitative approach with analytic descriptive data analysis. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The result of this research is the inculcation of the values of peace is included in the learning curriculum by teaching 12 values of peace. The achievements are to form the character of the santri (student) who is empathetic, independent, and courageous, capable of being a problem solver, critical, creative, communicative, and collaborative, as well as becoming a peacemaker and changemaker. The factor that supports the achievements of the inculcation of the values of peace is the Peacesantren Welas Asih that pays close attention to the quality of their abah ambu (teachers/coaches) to upgrade their knowledge and skills with the activities of Welas Asih Abah Ambu Academy (WAAAA) and collaborative parenting as a form of collaboration between schools and parents in educating students with Welas Asih Abah Ambu Academy (WAABA) activities. Basic peace value material is given during the orientation period of students with the name Welas Asih untuk Semesta (Compassion for the Universe). In this program, students and parents must be committed to supporting the implementation of anti-bullying policies and culture. Life skills-based education is applied in Peacesantren Welas Asih with an emphasis on 21’st century skills, namely literacy, competence, and character. The guidance follows 3 Guidance Pillars, namely, positive discipline, reflective relationship, and effective learning using the Project-based Learning, Problem-based Learning, and Discovery Learning models using the Design For Change method, with the FIDS (Feel, Imagine, Do and Share) learning system.